Correction: A lexicon-based diachronic comparison of emotions and sentiments in literary translation: A case study of five Chinese versions of David Copperfield. - Yan Li; Muhammad Afzaal; Yixin Yin (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0297101.].